Semi-quantitative risk assessment on Listeria monocytogenes in retail Chinese salads for Shanghai residents - Xia SONG; Hua CAI; Biyao XU; Baozhang LUO; Jingjin YANG; Hong LIU (Zhongguo shipin weisheng zazhi, 2020)
Objective To elucidate the prevalence of Listeria monocytogenes in Chinese salads in Shanghai, and to explore measures that can avoid cross-contamination and reduce the risk of infection caused by L. monocytogenes in salads. Methods Health risk and the influencing factors were estimated using a swift quantitative microbiological risk assessment (sQMRA) method with the prevalence of L. monocytogenes in Chinese salads collected from retail market in Shanghai, dietary consumption data and experimental data. Results The detection rate of L. monocytogenes in retail salads in Shanghai was 3.97% (6/151), the average concentration in contaminated samples was 60.53 CFU/g. For sensitive and non-sensitive people, the estimated incidence of nine different scenarios were 2.36×10-4-3.49×10-4 and 2.36×10-6-3.49×10-6, respectively, and the estimated cases were 162-431 and 6-17. Containers of different materials had different influence on the cross-contamination parameters of L. monocytogenes. The cross-contamination of the glass container was relatively high, and the estimated cases were the lowest. The cross-contamination parameters and ingestion of the ceramic containers were both low, and the estimated cases were the highest. After washing with sterile water or cleanser essence of the glass container and ceramic container, the estimated cases of L. monocytogenes infection were significantly reduced. Conclusion There was a certain risk of the contamination of L. monocytogenes in Chinese salads in Shanghai. Using glass containers and adopting cleaning measures could significantly reduce the number of cases of L. monocytogenes infection caused by cross-contamination during the preparation of Chinese salads in the kitchen.